The cytochrome d oxidase complex regulated by fexA is an Achilles' heel in the in vivo survival of Vibrio vulnificus. Issue 1 (1st January 2019) - Tan, Wenzhi; Jeong, Kwangjoon; Pendru, Raghunath; Puth, Sao; Hong, Seol Hee; Lee, Shee Eun; Rhee, Joon Haeng
ABSTRACT: Vibrio vulnificus is a halophilic estuarine bacterium causing severe opportunistic infections. To successfully establish an infection, V. vulnificus must adapt to redox fluctuations in vivo. In the present study, we show that deletion of V. vulnificus fexA gene caused hypersensitivity to acid and reactive oxygen species. The ΔfexA mutant exhibited severe in vivo survival defects. For deeper understanding the role of fexA gene on the successful V. vulnificus infection, we analyzed differentially expressed genes in ΔfexA mutant in comparison with wild type under aerobic, anaerobic or in vivo culture conditions by genome-scale DNA microarray analyses. Twenty-two genes were downregulated in the ΔfexA mutant under all three culture conditions. Among them, cydAB appeared to dominantly contribute to the defective phenotypes of the ΔfexA mutant. The fexA deletion induced compensatory point mutations in the cydAB promoter region over subcultures, suggesting essentiality. Those point mutations (Pcyd SMs) restored bacterial growth, motility, cytotoxicity ATP production and mouse lethality in the ΔfexA mutant. These results indicate that the cydAB operon, being regulated by FexA, plays a crucial role in V. vulnificus survival under redox-fluctuating in vivo conditions. The FexA-CydAB axis should serve an Achilles heel in the development of therapeutic regimens against V. vulnificus infection.